Fatty acid, mineral and heavy metal contents of different Malaysia fish species - Jaswir, Irwandi; Osman, Farida; Hashim, Ridzwan; Kitts, David D.; Chowdhury, Ahmed Jalal Khan (2010)
Fish are popularly recognized as an excellent source of lipids that are composed of a wide range of important fatty acids. Fish also contain good quality protein and are an adequate source of many vitamins (e.g. fat soluble A, D, E and the water soluble B-complex), in addition to important minerals such as calcium and phosphorous. We recently investigated the fatty acid (FA) profiles, mineral and heavy metal contents of 13 different species of commonly consumed, wild marine fin-fish found off Langkawi Island, a popular Malaysian tourist destination. The fish species were “jenahak” (Lutjanus agentimaculatus), “kebasi” (Anadontostoma chacunda), “duri” (Arius umatranus), “tenggiri batang” (Scomberomorus commersonii), “kembong” (Rastrelliger kanagurta), “kintan” (Psettodes crumei), “kerisi” (Pristipomoides typus), “kerapu” (Epinephelus sexfasciatus), “gelama keling” (Sciaena dussumieri),“malong” (Congresax talabon), “laban” (Cynoglossus lingua), “yu 9” (Scolidon sorrakowah) and “bagi” (Aacnthurs nigrosis). The overall findings reveal that all fish showed a considerable amount of unsaturated fatty acids particularly those with 4, 5 and 6 double bonds. Two physiologically important n-3 polyunsaturated fatty acids (PUFAs), i.e. eicosapentaenoic acid (EPA) and docasahaexaenoic acid (DHA), made up more than 50% of the total PUFAs. It can be concluded that fin fish found in Langkawi Island coastal areas are beneficial for human health as they have considerable amounts of PUFAs, especially AA and DHA fatty acids. In the case of heavy metal analysis, the result reveals the safety of the consumption of fish from the human health point of view